2020
DOI: 10.1002/aoc.5960
|View full text |Cite
|
Sign up to set email alerts
|

A self‐penetrating and chemically stable zinc (ii)‐organic framework as multi‐responsive chemo‐sensor to detect pesticide and antibiotics in water

Abstract: Guided by the self‐penetrating features can improve the stability of metal organic frameworks (MOFs), an unprecedented 3D self‐penetrated framework, {[Zn (tptc)0.5(bimb)]·H2O}n (NUC‐6, here NUC corresponding to North University of China), with 3D (4,4)‐c {86} net, was designed. Benefit from the high chemical stability and excellent luminescent property, NUC‐6 can be act as an efficient multi‐response chemo‐sensor in detecting dichloronitroaniline pesticide and nitrofuran antibiotics in water with the detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…6. Recent works have suggested that fluorescence is quenched when the analyte absorbs into the excitation wavelength range of the chemosensor, by the socalled internal filter effect (IFE) [68,69]. IFE is a process that can occur through two pathways: one requires the overlap between the absorption spectrum of the analyte (absorber) and excitation wavelength of the chemosensor (fluorophore); the another one involves the overlap of the absorption spectrum of the absorber with the emission spectrum of the fluorophore.…”
Section: The Sensing Mechanism Of 4-nitraniline (Pna)mentioning
confidence: 99%
“…6. Recent works have suggested that fluorescence is quenched when the analyte absorbs into the excitation wavelength range of the chemosensor, by the socalled internal filter effect (IFE) [68,69]. IFE is a process that can occur through two pathways: one requires the overlap between the absorption spectrum of the analyte (absorber) and excitation wavelength of the chemosensor (fluorophore); the another one involves the overlap of the absorption spectrum of the absorber with the emission spectrum of the fluorophore.…”
Section: The Sensing Mechanism Of 4-nitraniline (Pna)mentioning
confidence: 99%
“…As a representative of multifunctional crystalline materials, metal organic frameworks (MOFs) have attracted wide attention among researchers. In general, MOFs are constructed from metal ions and organic ligands through strong coordination bonds as well as weak interactions, and they have wide applications in the fields of chemical adsorption and separation, heterogeneous catalysis, chemical sensing, proton conduction, and supercapacitors. Besides, the unique structural features of a large surface area, high porosity, structure diversity, as well as active sites endow the MOFs themselves with a great potential as photocatalysts in the degradation of organic pollutants as well as electrocatalysts for overall water splitting. …”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) with charming topological architectures, high surface areas and porosities, and tunable pore structures can find huge potential applications in luminescent sensors, ion exchange, heterogeneous catalysis, gas storage, separation, etc. [5][6][7][8][9]. Currently, MOFbased photocatalysts are of current research interest owing to their high catalytic efficiencies and eco-friendly economic for the photocatalytic degradation of organic dye contaminants existing in the wastewater discharge [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%